2013
DOI: 10.2119/molmed.2012.00309
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Targeting Endogenous Secretory Receptor for Advanced Glycation End Products Rescues Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory synovitis that leads to the destruction of bone and cartilage. The receptor for advanced glycation end products (RAGE) is a multiligand membrane-bound receptor for high-mobility group box-1 (HMGB1) associated with development of RA by inducing production of proinflammatory cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-1 and IL-6. We developed a bone-targeting therapeutic agent by tagging acidic oligopeptide to a nonmem-brane-bound form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…D6-esRAGE administered weekly (1 mg/kg) to RA model mice was able to reduce inflammatory arthritis, synovial hyperplasia, cartilage destruction, and bone destruction. D6-esRAGE also reduced plasma levels of proinflammatory cytokines (TNF)-α, IL-1, and IL-6 [64]. Thus, it was shown that D6-esRAGE greatly facilitated drug delivery to bones.…”
Section: Non-enzymatic Glycosylation and Advanced Glycation End Productsmentioning
confidence: 95%
“…D6-esRAGE administered weekly (1 mg/kg) to RA model mice was able to reduce inflammatory arthritis, synovial hyperplasia, cartilage destruction, and bone destruction. D6-esRAGE also reduced plasma levels of proinflammatory cytokines (TNF)-α, IL-1, and IL-6 [64]. Thus, it was shown that D6-esRAGE greatly facilitated drug delivery to bones.…”
Section: Non-enzymatic Glycosylation and Advanced Glycation End Productsmentioning
confidence: 95%
“…HMGB1 forms complexes with IL-1α, IL-1β, and LPS to enhance immune and inflammatory responses at the joint (Qin et al, 2014; Wahamaa et al, 2011). Moreover, therapeutic targeting of HMGB1 (e.g., HMGB1 neutralizing antibodies, recombinant A box, recombinant thrombomodulin, soluble RAGE, oxaliplatin, gold salts, and glucocorticoid) inhibits HMGB1 release and activity, which prevents the progression of arthritis in experimental animals (af Klint et al, 2005; Bossaller and Rothe, 2013; Goldstein et al, 2007; Hamada et al, 2008; Ostberg et al, 2010; Ostberg et al, 2008; Takahashi et al, 2013b; Yuan et al, 2008; Zetterstrom et al, 2008). These findings suggest that HMGB1 is an important target in the treatment of rheumatoid arthritis (Andersson and Harris, 2010).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…Recently, a novel bone-targeting peptide has been attached to an enzyme (alkaline phosphatase) and shown that the tagged enzyme is delivered more specifically to bone than unmodified native enzyme. This tagged enzyme improves the clinical and pathological consequence of systemic bone disease, hypophosphatasia and osteoarthritis [31,32,38]. A clinical trial for hypophosphatasia using this bone-targeting system showed substantial improvement of bone pathology and was clinically effective [33].…”
Section: Advanced Therapies For Morquio a Syndromementioning
confidence: 99%
“…Specific delivery of drugs to avascular cartilage tissue has not yet been attained, although several promising results targeting drugs to bone to treat a range of bone diseases have been demonstrated to be effective both experimentally and clinically [26,31-38,9]. …”
Section: Introductionmentioning
confidence: 99%